Nnc Z∗-open sets in Nnc Topological Spaces - et. al., K. Balasubramaniyan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to introduce and study the notion of NncZ∗o-sets in Nnc topological space. Some characterizations of these notions are presented